تقييم دور الخدمة الاجتماعية الطبية في الرعاية الصحية الأولية من وجهة نظر الأخصائيين الاجتماعيين والمرضى (Comprehensive Journal of Science, 2026)
This research examines the role of medical social services in primary health care from the perspectives of social workers and patients. The research problem crystallized in answering the following question :What is the evaluation of the role of medical social services in primary health care from the perspectives of social workers and patients? The research community included all social workers and patients at health care centers and hospitals in Benghazi. This research relied on a descriptive analytical approach, which relies on studying reality, or the phenomenon as it exists in reality, and aims to provide an accurate description. The research reached a number of results, the most important of which are :1- The study sample members generally agree with the tasks and activities performed by social workers in the field of medical social work.2- The study sample members are satisfied with the role of social workers in healthcare centers and hospitals.3- The study sample members who are social workers are satisfied with the role of social workers in healthcare centers and hospitals.4- The study sample members agreed that there are obstacles facing the work of social workers in the medical field in general.Based on these results, the study made the following recommendations:1- Providing a sufficient number of medical social workers, depending on the services provided by the center or hospital.2- Working to develop the professional and academic skills of medical social workers.3- Working to keep pace with scientific developments in medical social services.